Identification of PP1y2 interacting proteins from human testis using the yeast two-hibrid system - Mota, Catarina Figueiredo da
Protein phosphorylation is a major eukaryotic control mechanism. As knowledge on the molecular basis of disease expands, misregulation of normal phosphorylation/dephosphorylation control mechanisms is discovered to underlie an increasing number of pathologies. Key target proteins are subject to reversible phosphorylation catalysed by protein kinases and protein phosphatases. Any disruption of the fine balance between kinase and phosphatase activities can have disastrous consequences for the cell. Protein phosphatase activity is often regulated by binding to specific regulatory proteins. In mammalian sperm, PP1g2 is known to be the major type 1 Protein Phosphatase and to regulate sperm motility, probably through binding to one or more regulatory protein subunits. A specific regulator of this isoform, involved in the control of sperm motility, would be an attractive therapeutic target for the treatment of some forms of male infertility, or for the development of a new class of male contraceptives. To this end, a Yeast Two-Hybrid screen was performed to identify human sperm-specific PP1g2 regulators, in an effort to elucidate the biochemical mechanisms controlling sperm function and development. Screening of approximately 2.5x107 clones from a human testis cDNA library with the Cterminal specific domain of PP1g2 yielded 85 positive clones that were analysed to identify novel testis-specific PP1 regulators that might be involved in the control of sperm motility. Several proteins interacting specifically with this isoform were recognized by alignment with the GenBank database records and future studies will address their involvement in PP1g2-controlled events leading to sperm maturation and control of motility.